Nutrient Management for Sustainable Production of Sweet Potato (Ipomoea batatas L.) in Saline Inceptisols of West Bengal - Laxminarayana, K.; Burman, D. (JOURNAL OF ROOT CROPS, 2013)
A field experiment was conducted for two consecutive rabi (winter) seasons during 2009-2010 and 2010-2011 in a natural saline Inceptisol to optimize the requirement of N and P for sustainable production of sweet potato. The results revealed that the mean tuber and vine yields increased significantly with increasing doses of N and P up to 50 kg ha-1. Higher tuber yield (19.65 t ha-1), total uptake of N (73.75 kg ha-1) and N use efficiency (143.4 kg tubers per kg N) was observed due to the combined application of 50 kg each of N and P2O5 ha-1. Significantly highest mean starch content (22.55 %) was obtained due to the application of N and P2O5 @ 50 and 75 kg ha-1, respectively, while the highest dry matter content (31.45 %) was observed due to the combined application N and P2O5@ 50 kg ha-1 each. Significantly highest P and K uptake was observed due to the application of 75 kg ha-1 each of N and P2O5. Highest P use efficiency (87.0 kg tubers per kg P2O5) was observed due to the application of 75 and 25 kg ha-1 of N and P2O5 respectively. Application of N and P2O5 @ 50 kg ha-1 each was found to be optimum for sustainable production of sweet potato with good quality tubers and higher nutrient use efficiency. Further, this recommendation offers good scope for food and nutritional security in the saline tracts of Eastern India.